The Algarve climatophilous vegetation series – Portugal: a base document to the planning, management and nature conservation Les séries de végètation climatophiles de l’Algarve - Portugal: un document de base pour la planification, gestion et conservation de la nature - Quinto-Canas, Ricardo (2013)
This work was developed as part of PhD research devoted to the flora and vegetation of the Caldeirão and Monchique mountains that aims to identify the vegetation climatophilous series and use them as an environmental diagnosis of Algarve administrative province phyto-ecological subregions. Biogeographic and bioclimatic considerations are presented, as well as the study area pedological and lithological characterization. For each of the seven climatophilous series the dynamic and catenal behaviours, as well as the main characteristic plants that constitute the successional stages, are given. The corresponding patrimonial value is studied.